Introducing a Talent Management Model based on Grounded theory (Case Study: Telecom Operator) - Ariyan Gholipor; Nayere Eftekhar (پژوهش‌های مدیریت عمومی, 2017)
Extended Abstract Changing economic and technological paradigms, causes very significant issues in different industries, especially technology-laden ones, like telecom. One of the most important issues is talent management; acquisition, development and retention of talents. This is because after McKinsey’s talent war notion, many companies, adopt focused efforts and investment in this part of human resource management of their companies. Academic researchers also entered the field and tried to explore different aspect of talent management. However, as Tarique and Schuler (2010) mentioned, there is not enough qualitative research in the field and most of the researches are based on North-America culture. On the other hand, most of the introduced models are manifesting an ideal model of talent management and did not notice the current condition of the phenomenon in the organizations. Based on this issues, we tried to develop a talent management model based on grounded theory for a telecom operator   Case of the study The research was conducted in the third mobile operator of Iran. This operator has been chose, because it is younger than others and do not have established talent management procedures   Method and Measurement 25 in-depth interview was conducted with different stakeholders of talent management in the case. Interviews was conducted with managers in different levels, professional talents and HR experts. The Research Method was grounded theory, based on Corbin and Strauss (2015) version. The evaluation of the rigor and validity of our results based on this version validity indexes   Discussion and Results The final Finding was a comprehensive model of current condition of talent management in the telecom operator. The process model was based on conditions, action-interaction, and consequence parts that is mentioned in Corbin and Strauss (2015) as the ideal type of a process. The talent management procedures, were different in different department based on their managers’ viewpoint. Three category of condition was found: talent characteristics (what is known as talent in organization), management and Organization maturity level. In Action-Interaction, three main procedures of talent management system is introduced (Talen acquisition, talent development and talent retention). The consequence of these action-interaction was employer brand, talents’ self-actualization and organization success. All of this has a cultural background that impact all of the aspects of the model.   Conclusion Notice this important point that talent management is not a rigid process in organization and cultural factors affect all of its aspect, is the main conclusion of this paper. The quality of talent management is in direct relation with what organization and departments’ manager think about the subject. So for establishing a talent management system in the organization, the first and the most important aspect is to make a common language on the issue.